Host-guest complexes of two isomeric 2,2’-bioxazole based 2-lehn-type cryptands. Prediction of ion selectivity by quantum chemical calculations. Part XIV - Ćoćić, Dušan; Siegl, Selina; Manaa, Aliya; Begel, Svetlana; Hubbard, Colin D.; Puchta, Ralph (Journal Macroheterocycles, 2020)
The two isomeric cryptands 1 (N,N’-bis(2,2’-bioxazole-5,5’-dimethyl)-2,2’-bioxazole-5,5’-bis(methylamine)) and 2 (N,N’-bis(2,2’-bioxazole-4,4’-dimethyl)-2,2’-bioxazole-4,4’-bis(methylamine)) were investigated by DFT-calculations (RB3LYP/LANL2DZp). Based on these structures and energies we have determined with model equations and by structural comparison with solvent complexes ([M(Furan)n ]m+, [M(Pyridine)n]m+ and [M(NH3)n]m+) the ion selectivity of 1 and 2. 1 exhibits preferences for the sodium cation and the calcium dication, nearly equally with the strontium dication. Therefore, 1 has a cavity comparable to [phen.phen.phen]. In contrast, cryptand 2, although it also shows a preference for the third-row sodium cation, for the third-row alkaline earth cation Mg2+. Therefore, the cavity size must be similar to that of Bühl’s cryptand dodeka(ethylene)octamine and [2.1.1]. We attribute this difference in selectivity to the longer Mm+-N-interactions in 2 compared to Mm+-O-interactions in 1.
CRIS-Team Scopus Importer:2020-12-18
Keywords: Cryptand; DFT-study; Selective ion complexation